Enhancing sustainable agriculture through innovative packaging: consumer preferences and willingness to pay in the Nepalese market - Anisha Giri; Tilak Raj Chaulagai (Cogent Food & Agriculture)
This study investigates the consumer preferences for packaged agricultural products in Nepal, examining how advanced packaging solutions can align with the emerging sustainable consumption patterns. Employing a combination of online surveys and face-to-face interviews, the research explores the willingness of consumers to invest in packaging attributes that promote environmental sustainability, convenience and information transparency. Utilization of the ordered logit regression model reveals a positive consumer disposition towards eco-friendly packaging materials, clear labeling of product information and ease of use. The study uncovers a robust willingness among consumers to pay a premium for these innovative packaging features, emphasizing the need for industry stakeholders to incorporate sustainability into packaging design. The findings suggest that consumers are willing to pay up to 20% more for products with green packaging initiatives, showcasing the potential to leverage such preferences in support of sustainable agricultural practices and reduction of post-harvest losses in Nepal and potentially in similar markets globally.